Seasonal patterns of infectious diseases in Riyadh Province, Saudi Arabia: a retrospective analysis - Mansour Almuqbil; Syed Imam Rabbani; Faisal Ghazi Alharbi; Meshari Hajed Alharbi; Rafiulla Gilkaramenthi; Amro Mohammed Sawadi Khormi; Mutlaq Eidhah M. Almalki; Walaa F. Alsanie; Abdulhakeem S. Alamri; Majid Alhomrani; Amal F. Alshammary; Syed Mohammed Basheeruddin Asdaq (Critical Public Health)
This study investigated the seasonal impact on the prevalence of infectious diseases in the Riyadh Province of Saudi Arabia. The study retrieved data from official websites and articles to analyse the incidence of microbial infections attributed to bacteria, viruses, fungi, and protozoa across various months of the year. The data was statistically analysed by one-way analysis of variance followed by chi-square and Pearson’s correlation coefficient tests. Correlation analysis, utilizing an established method and setting significance at P < 0.05, examines the relationship between infectious diseases and climatic conditions. The findings revealed an elevated incidence of microbial infections during specific months of the year. Correlation analysis indicated a significant likelihood of bacterial infection in June (OR 1.08), July (OR 1.12), August (OR 1.19), and September (OR 1.09). Similarly, viral infections peaked in December (OR 1.13), January (OR 1.28), February (OR 1.21), and March (OR 1.14), while fungal infections showed an increased frequency in July (OR 1.07) and August (OR 1.09). However, precise seasonal patterns of protozoan infections have not been discerned. This finding suggests that certain pathogens may exhibit heightened activity at certain times of the year. Such insights into the temporal dynamics of infectious diseases have significant implications for public health. Implementing timely interventions, including vaccination campaigns, heightened surveillance efforts, and targeted hygiene protocols, could potentially mitigate the spread of infectious agents and alleviate the burden on healthcare systems. Consequently, this study contributes valuable knowledge that can inform proactive strategies aimed at reducing the overall impact of infectious diseases on public health.